Ação de polissacarídeos sulfatados de Fucus Vesiculosus na Hemostasia e no sistema complemento - Azevedo, Tarciana Carvalho Gurgel de (2006)
Fucans are a family of sulfated homo and teropolysaccharides respectively, composed mainly of a- (1®2) and a- (1®3) linked by L-fucose residues. Properties such as the ability to act as an anti-contraceptive, to reduce cholesterol levels, and to act as an anti-tumor agent are much related. We have focused our attention on the anticoagulant properties, platelet aggregation, hemorrhagic activity and complement system in vitro of commercial fucoidan (F) and their purified fractions (F1, F2 and F3) from Fucus vesiculosus obtained from fractionation of the fucoidan with different concentrations of acetone 1, 2 and 3v. These compounds were chemically characterized and the fucoidan (F) was modified by desulfation. The anticoagulant activity of the compounds was assessment by activated partial thromboplastin time (APTT) and prothrombine time assay (PT) using citrated normal human plasma. The results of APPT test showed that F, F1 and F2 have high anticoagulants activities 240.0 s (5 µg). The F3 showed 73.7 s in the same concentrations. The results obtained with PT test to F, F1, F2 and F3 were 81.5 s, 120.0 s, 57.1 and 32.5 s respectively with 50 µg. The dessulfated polymer showed a decrease in the anticoagulant activity in these two tests. Platelet aggregation assay was measured turbidimetrically with platelet aggregometer by method of Born. The aggregation platelet with F and fractions F1, F2 and F3 exhibited a two-phase answer in the concentration of 5 mg/mL with maximum aggregation of 76.36 ± 10.3% ; 69.54 ± 9.40%; 75.94 ± 9.01%; 51.13 ± 9.59% respectively. However, was observed a hipoaggregate profile F (15.17 ± 5.2%), F1 (7.40 ± 3.04 %), F2 (19.1 ± 5.41%) and F3 (5.09 ± 3.02%) at 0.1 mg/mL. The hemorrhagic activity assay was carried in Wistar rats and showed that these compounds have low hemorrhagic effect when compared to heparin. The complement system ( alternative pathway was made using non-sensibilized rabbit red blood cells The results of complement system essay showed that F , F2 and F3 have action inhibitory in relation to the group control 0.544, 0.697, 0.622 and 0.958 respectively The results showed that these compounds have action on this system. Interaction of the polisaccharides with proteins C3 and C4 showed that the fraction F1 stimulated the activity assay hemolytic using red blood cells